2017
DOI: 10.1093/ndt/gfx244
|View full text |Cite
|
Sign up to set email alerts
|

Measured (and estimated) glomerular filtration rate: reference values in West Africa

Abstract: Normal GFR values and descriptions of percentiles are now available for West Africa. As in Caucasians, no significant difference was observed between men and women. Moreover, the same age-associated decline in mGFR is also observed after 40 years of age, as in Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
3
29
1
Order By: Relevance
“…This observation confirmed limited previous data suggesting that SCr normal values were comparable in Africa and Europe. 17,31 Regarding reference values, we also confirmed that healthy people from West Africa or Central Africa have the same distribution of mGFR as Whites, 17,18 notably with the same decrease in mGFR with aging. 32 Among the different SCr-based equations, both CKD-EPI and FAS-SCr equations had the same performance in the whole population and in subjects with GFR >60 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This observation confirmed limited previous data suggesting that SCr normal values were comparable in Africa and Europe. 17,31 Regarding reference values, we also confirmed that healthy people from West Africa or Central Africa have the same distribution of mGFR as Whites, 17,18 notably with the same decrease in mGFR with aging. 32 Among the different SCr-based equations, both CKD-EPI and FAS-SCr equations had the same performance in the whole population and in subjects with GFR >60 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 78%
“…21 Previous data from Africa (and African European) also suggested that such an ethnic factor was not valuable. [18][19][20][21][22]29,30 Regarding ethnicity, we showed that FAS SCr af had the same global performance as FAS SCr observed in Whites, both in patients with low GFR values and in subjects with high GFR values. This is easily explained, as Q af was not different from the Q values observed in Whites.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations